2022
DOI: 10.3389/fpsyg.2022.856558
|View full text |Cite
|
Sign up to set email alerts
|

The Proactive-Reactive Resilience as a Mediational Variable Between the Character Strength and the Flourishing in Undergraduate Students

Abstract: The aim of this research was to delimit the predictive and mediational model of resilience between character strengths to predict flourishing, in a sample of undergraduate students. After signing their informed consent, 642 university students completed three validated scales (i.e., character strengths, resilience, and flourishing). Using an ex post facto design, regression, structural modeling, and mediation analyses were carried out, in order to construct a multi-causal predictive model. Results indicated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 92 publications
0
12
1
5
Order By: Relevance
“…In the SEM model, the results established the relationship between Chinese virtues and student resilience and indicated that Chinese virtues positively affected students’ positive resilience, which is consistent with previous studies [ 37 , 38 ]. Surprisingly, this study identified a direct positive effect of Chinese virtues on students’ succumbing; this may not be consistent with previous studies [ 55 ] that found that character strengths (i.e., the different aspects of virtues), as a multidimensional construct, significantly and jointly predicted resilience. The opposite results in this study might be partly due to Chinese Confucian culture.…”
Section: Discussioncontrasting
confidence: 99%
“…In the SEM model, the results established the relationship between Chinese virtues and student resilience and indicated that Chinese virtues positively affected students’ positive resilience, which is consistent with previous studies [ 37 , 38 ]. Surprisingly, this study identified a direct positive effect of Chinese virtues on students’ succumbing; this may not be consistent with previous studies [ 55 ] that found that character strengths (i.e., the different aspects of virtues), as a multidimensional construct, significantly and jointly predicted resilience. The opposite results in this study might be partly due to Chinese Confucian culture.…”
Section: Discussioncontrasting
confidence: 99%
“…The proposed Conceptual Utility Model ( de la Fuente et al, 2022a , b , c ; de la Fuente and Martínez-Vicente, 2023a , b , c ) aims to address and overcome the above limitations in an integrative heuristic based on prior evidence ( de la Fuente, 2021 ). It seeks to provide a general model applicable in different psychological fields, and to be both protective and predictive of stress and psychological wellbeing:…”
Section: Theoretical Basismentioning
confidence: 99%
“…Resiliensi merupakan faktor yang berkontribusi terhadap flourishing [20]. Hal tersebut dipertegas oleh pendapat ahli sebelumnya bahwa perkembangan flourishing terjadi karena individu memiliki kemampuan resiliensi dalam beradaptasi dengan kondisi di lingkungan [21].…”
Section: Pendahuluanunclassified
“…Resiliensi mencakup dimensi kegigihan, kontrol, perubahan, stres dan spritual menunjukkan pengaruh positif signifikan terhadap flourishing. Dimensi kegigihan dan perubahan memiliki pengaruh paling kuat dalam mempengaruhi flourishing dibanding kontrol, stres dan spritual [20].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation